The effect of knowledge transfer theory on the selection of crossover winter sports athletes: A systematic literature review - Gao, Yongqi; Soh, Kim Geok; Zakaria, Noor Syamilah; Mohd Rasdi, Roziah; Guo, Wei; Soh, Kim Lam (Frontiers in Psychology, 2023)
This paper reviews the studies of knowledge transfer theory (KTT) in other disciplines through the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) and identifies the research gap. A systematic process was used to search the literature in six different databases aimed to clarify the relationship between KTT and crossover selection, promote crossover development of winter sports and cultivate outstanding athletes. This paper provides the foundation for the study of KTT in the field of selection of athletes for professional sports with the intension to apply KTT in the field of sports and showcase KTT’s success in the selection of winter sports athletes. Crossover selection of qualified athletes solves the issue of shortage of professional athletes in specific sports.